Auf dem Weg zum Closed-Loop – Ziel und Realität - Biester, Torben; Danne, Thomas; Kordonouri, Olga (DMW - Deutsche Medizinische Wochenschrift, 2017)
An old dream of patients with type 1 diabetes and medical teams alike is a fully automated insulin therapy. Available sensor-augmented insulin-pumps are able to intervene in insulin therapy by reducing the dose. Aim of several studies is to add an algorithm to the interaction of pump and sensor, so that insulin doses can be regulated fully automatically. Totally closed loop systems are currently not yet available for outpatient use. Hybrid closed loop systems have been approved in the US. They can improve the metabolic status of patients with type 1 diabetes. Risks are similar to sensor-augmented insulin-pump therapy. Patients’ detailed education will continue to be essential for success.
Keywords: CGM; CSII; Glukosesensor; Closed Loop; Hybrid-closed Loop; SuP